2013
DOI: 10.1055/s-0032-1327626
|View full text |Cite
|
Sign up to set email alerts
|

Two Challenge and Rechallenge Episodes of Chloroquine-Induced Psychotic Mania in a Patient with Rheumatoid Arthritis

Abstract: Chloroquine, an anti-malarial drug, is also used in the treatment of rheumatoid arthritis. It has been known for decades that chloroquine could cause psychiatric side effects; however, reports are scarce. This report concerns a rare case of 2 challenge and re-challenge episodes of mania during chloroquine treatment of rheumatoid arthritis. Some hypothetical pathophysiological mechanisms that may lead to these adverse effects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The symptoms may develop once CQ is reintroduced. Six individuals suffered from psychiatric adverse effects at different time points: 3 years, 64 15 months, 6 and 5 years 47 before the case report; and 3 weeks 65 after the first case. The reports indicated that, in some instances, individuals had taken CQ before the case report without having any complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms may develop once CQ is reintroduced. Six individuals suffered from psychiatric adverse effects at different time points: 3 years, 64 15 months, 6 and 5 years 47 before the case report; and 3 weeks 65 after the first case. The reports indicated that, in some instances, individuals had taken CQ before the case report without having any complications.…”
Section: Resultsmentioning
confidence: 99%
“…One study 79 reported a suicide attempt. Psychiatric adverse effects for 3 case reports reemerged, respectively, in 2 weeks, 72 3 weeks, 65 3 months, 68 and 5 years 8 after HCQ was reintroduced. Ten individuals received antipsychotic drugs to treat the symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…It must be considered that chloroquine (CQ) used for the treatment of vivax malaria may have as an adverse event psychiatric and nervous system disorders, which may reflect on changes in cognitive and executive functions during the treatment of vivax malaria 66 , 67 . Since only the patients exposed in this study had previous malaria, they are in an endemic area, where CQ has been the treatment of first choice for many years and low CQ resistance is defined, we consider that CQ may potentially play an important role in altering neurocognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of neurological and psychiatric events was described in patients treated with CQ for malaria, amoebiasis, arthritis, acute myocardial infarction, erythema nodosum leprosum, or COVID-19 [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 125 , 193 , 195 ]. Nevertheless, in the case of treatment with HCQ, only one case of psychomotor agitation in a patient with RA and one case of psychosis in a patient with SLE were reported [ 74 , 93 ].…”
Section: Resultsmentioning
confidence: 99%